Phase changing nanocomposites for low temperature thermal energy storage and release - A. Dorigato; P. Canclini; S. H. Unterberger; A. Pegoretti (eXPRESS Polymer Letters, 2017)
The aim of this paper is to develop new elastomeric phase change materials (PCM) for the thermal energy storage/release below room temperature. In particular, poly(cyclooctene) (PCO)/paraffin blends filled with various concentrations of carbon nanotubes (CNTs), were prepared by a melt compounding process. The microstructural, thermo-mechanical and electrical properties of the resulting materials were investigated. The microstructure of these materials was characterized by the presence of paraffin domains inside the PCO, and CNTs were located only inside the paraffin domains in forms of aggregated clusters. DSC tests evidenced the existence of two distinct crystallization peaks at –10 and at 6 °C, respectively associated to the paraffin and the PCO phases, indicating that both the polymeric constituents are thermally active below room temperature. Moreover, CNT addition did not substantially alter the melting/crystallization properties of the material. Noticeable improvements of the mechanical properties and of the electrical conductivity with respect to the neat PCO/paraffin blend could be obtained upon CNT addition, and also thermal conductivity/diffusivity values were considerably enhanced above the percolation threshold. Finite element modeling demonstrated the efficacy of the prepared nanocomposites for applications in the thermal range from –30 to 6 °C.